Luminal microbiota related to Crohn's disease recurrence after surgery. (1st November 2020) - Hamilton, Amy L.; Kamm, Michael A.; De Cruz, Peter; Wright, Emily K.; Feng, Hai; Wagner, Josef; Sung, Joseph J. Y.; Kirkwood, Carl D.; Inouye, Michael; Teo, Shu-Mei
ABSTRACT: Background: Microbial factors are likely to be involved in the recurrence of Crohn's disease (CD) after bowel resection. We investigated the luminal microbiota before and longitudinally after surgery, in relation to disease recurrence, using 16S metagenomic techniques. Methods: In the prospective Post-Operative Crohn's Endoscopic Recurrence (POCER) study, fecal samples were obtained before surgery and 6, 12, and 18 months after surgery from 130 CD patients. Endoscopy was undertaken to detect disease recurrence, defined as Rutgeerts score ≥i2, at 6 months in two-thirds of patients and all patients at 18 months after surgery. The V2 region of the 16S rRNA gene was sequenced using Illumina MiSeq. Cluster analysis was performed at family level, assessing microbiome community differences between patients with and without recurrence. Results: Six microbial cluster groups were identified. The cluster associated with maintenance of remission was enriched for the Lachnospiraceae family [adjusted OR 0.47 (0.27–0.82), P = .007]. The OTU diversity of Lachnospiraceae within this cluster was significantly greater than in all other clusters. The cluster enriched for Enterobacteriaceae was associated with an increased risk of disease recurrence [adjusted OR 6.35 (1.24–32.44), P = .026]. OTU diversity of Enterobacteriaceae within this cluster was significantly greater than in other clusters. Conclusions: Luminal bacterial communities are associated with protection from, and the occurrence of, Crohn's disease recurrence after surgery. Recurrence may relate to a higher abundance of facultatively anaerobic pathobionts from the Enterobacteriaceae family. The ecologic change of depleted Lachnospiraceae, a genus of butyrate-producing bacteria, may permit expansion of Enterobacteriaceae through luminal environmental perturbation.